Band 3 - Möller, Horst; Cubar'jan, Aleksandr O. (Mitteilungen der Gemeinsamen Kommission für die Erforschung der jüngeren Geschichte der deutsch-russischen Beziehungen, 2023)
The German-Russian Historical Commission, a body of experts appointed by both governments, promotes research into mutual relations in the 20th century, among other things through joint projects and international colloquia. The 3rd volume of the "Mitteilungen" focuses on the contributions of the 4th scientific colloquium held in Moscow in 2003 on the topic: "The USSR and the Reunification of Germany".